Bandwidth Improvement on Rectangular Monopole Antenna using Dual Bevel Technique for Ultrawideband Technology - Liya Yusrina Sabila; Damayanti, Denti Agustina; Prakoso, Teguh (Mobile and Forensics, 2022)
This paper presents the analyzed Monopole Antenna for Ultrawideband with a rectangular patch design using bevel technique at a frequency of 3.1 – 10.6 GHz. The fabricated antennas with dual bevel angles have a very compact width and length of 40 mm x 33 mm respectively and a groundplane width of 13 mm. To get bandwidth improvement on monopole antennas can be applied to the bevel angle on the patch. So, to get the best antenna design, 3 optimizations of antenna size changes were carried out during the simulation, that is optimization of patch length, patch width and bevel angle. Variation of patch length and width is used to change the frequency range and variation of bevel angle to increase bandwidth. From each change, the best result is taken. The experiment obtained the best simulation result of antenna and then fabricate it. From the measurement results on the fabricated antenna, the lowest S11 value is -24.6 dB, gain 2.6 dBi at a frequency of 5 GHz and radiation pattern is omnidirectional. The optimization process using the bevel technique has been proven to be successful in shifting the frequency range by around 600 MHz and increasing the bandwidth by about 4% or 30 MHz.